Respuesta :

Answer:

c

Step-by-step explanation:

[tex]x=5+i\sqrt{7} , y = 5-i\sqrt{7}\\ x^2-2xy+y^2=(x-y)^2\\ (x-y)^2=(2i\sqrt{7} )^2\\4.i^2.7\\-28[/tex]

Answer:

c

Step-by-step explanation:

given x = 5 + i[tex]\sqrt{7}[/tex] then y = 5 - i[tex]\sqrt{7}[/tex]

x² - 2xy + y² ← is a perfect square

= (x - y)² ← substitute values for x and y

= (5 + i[tex]\sqrt{7}[/tex] - (5 - i[tex]\sqrt{7}[/tex] )²

=  (5 + i[tex]\sqrt{7}[/tex] - 5 + i[tex]\sqrt{7}[/tex] )²

= (2i[tex]\sqrt{7}[/tex] )²

= 2² × i² × ([tex]\sqrt{7}[/tex] )²

= 4 × - 1 × 7

= - 28